DIGITAL HEARING AID SIGNAL PROCESSING SYSTEM USING ANDROID PHONE - GOH, YEH-HUANN; LEE, YOON-KET; YIP, MUM-WAI; E. U., KOK-SENG; GOH, YANN LING; LUM, KIN-YUN (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this research is to propose an Android-based digital hearing aid signal processing algorithm with following key features: (1) Regenerated audio match the patient-specific pattern of hearing loss, (2) noise reduction, and (3) provide flexibility to the users. Methods: The proposed signal processing algorithm is designed based on the specific hearing loss of the hearing disorder patient using inverse Fourier transform; besides, noise reduction feature is included in the digital algorithm design as well. Proposed digital algorithm has been implemented into an Android-based smartphone and its performance has been tested under real-time condition. Results: Simulation results show that the frequency response of the proposed digital hearing aid signal processing algorithm is in agreement with the initial theoretical design that was carried out based on the hearing impaired patient’s audiogram. The proposed algorithm has been implemented in the Android-based smartphone and tested in real time. Results show that most of the patients are satisfied with the regenerated audio quality. According to patient’s comments, the regenerated audio is clear and the users are allowed to control the volume level. Besides, no obvious hearing latency can be detected. Conclusion: Audio signals generated by the proposed digital signal processing algorithm show similar audio signal frequency response in both theoretical design and MATLAB simulation results. The only difference between the design and simulation results is the amplification levels. The proposed algorithm provides flexibility to the users by allowing them to choose the desired amplification level. In real-time testing, the proposed Android-based digital hearing aid is able to reduce noise level from the surrounding and the output processed speech match the patient-specific hearing loss.